2021
DOI: 10.46542/pe.2021.211.723730
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students’ perceptions of collaborations, barriers, and attitude towards patient-centred care in persons with mental disorder in south-west Nigeria

Abstract: Introduction: Patient-centred care is critical for enhanced management of mental disorders, this proves the need for an adequate understanding of students’ attitudes and view about it. Aim: The study assessed pharmacy students’ perceptions of collaborations, barriers, and attitudes towards patient-centred care in persons with mental disorders. Methods: Cross-sectional study was conducted among 87 final year pharmacy students. Descriptive analysis was performed using SPSS version 15.0. Average scores of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This corroborates findings from a previous study of pharmacy students in Nigeria. 29 Although students have limited understanding and experience of the healthcare system, the similarity in desired collaborations with licensed pharmacists is remarkable. A previous study in Nigeria reported positive attitude and physicians’ willingness to collaborate with hospital pharmacists in multidisciplinary ward rounds and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates findings from a previous study of pharmacy students in Nigeria. 29 Although students have limited understanding and experience of the healthcare system, the similarity in desired collaborations with licensed pharmacists is remarkable. A previous study in Nigeria reported positive attitude and physicians’ willingness to collaborate with hospital pharmacists in multidisciplinary ward rounds and patient care.…”
Section: Discussionmentioning
confidence: 99%